2016
DOI: 10.1007/s40596-016-0592-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brief Psychoeducational Program on Stigma in Malaysian Pre-clinical Medical Students: A Randomized Controlled Trial

Abstract: Our findings provide additional evidence that educational lecture on mental illness, coupled with either face-to-face contact or video-based contact, is predictive of positive outcomes in anti-stigma programs targeting future healthcare providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 37 publications
1
53
1
Order By: Relevance
“…This implies that primary care nurses in Penang have more stigmatising attitudes towards people with mental illness compared to Canadian HCPs. Our figures were however lower than those found on a recent study on Malaysian medical students which utilised the same scale [ 67 ]. Taken together, it appears that significant stigmatising attitudes towards people with mental illness are prevalent among nurses and future doctors in Malaysia, a finding which is consistent with local and international studies [ 4 , 29 , 31 , 34 ].…”
Section: Discussioncontrasting
confidence: 95%
“…This implies that primary care nurses in Penang have more stigmatising attitudes towards people with mental illness compared to Canadian HCPs. Our figures were however lower than those found on a recent study on Malaysian medical students which utilised the same scale [ 67 ]. Taken together, it appears that significant stigmatising attitudes towards people with mental illness are prevalent among nurses and future doctors in Malaysia, a finding which is consistent with local and international studies [ 4 , 29 , 31 , 34 ].…”
Section: Discussioncontrasting
confidence: 95%
“…The authors reported a statistically significant change in one out of seven items of a social distance questionnaire between pre-assessment and 1-month follow-up. By contrast, Fernandez et al (2016) found more robust results of a contact intervention. They compared a face-to-face with a video-based contact intervention in a randomised controlled trial with medical students.…”
Section: Resultsmentioning
confidence: 83%
“…One study found a significant change in only one out of seven items measuring social distance after a face-to-face contact intervention (Altindag et al, 2006). Another study found no statistical difference between a face-to-face and video-based contact intervention (Fernandez et al, 2016). In a previous systematic review, Yamaguchi et al (2013) had identified two studies comparing face-to-face v .…”
Section: Discussionmentioning
confidence: 99%
“…The studies were published, in order of frequency, in Europe (14), Asia (11), and North America (7), plus a few contributions in Africa (3), Oceania (2) and Latin America (1). The rank is different if we consider the number of students who participated in the studies, with Asia 15,23,24,16,17 in the first position (6492), followed by Europe 13,14,7 (5730), North America (2887) and Oceania 24 (2521), and finally by Africa 23,25 and Latin America (398 and 21 students, respectively). Little research is found from low and middle income countries 3 , in spite of the fact that these are the countries in which medical students endorse more stigma attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to their geographic location, the studies are distributed among 20 countries worldwide. With regard to the continental (Geographic/Cultural) distribution, Europe 13,14,7 ranks first (37%), followed by Asia 15,16,6 (29%) and North America (18%). (Figure 2.…”
Section: R E S U L T Smentioning
confidence: 99%